Reconstruction of the mouse extrahepatic biliary tree using primary human extrahepatic cholangiocyte organoids - Sampaziotis, Fotios; Justin, Alexander W.; Tysoe, Olivia C.; Sawiak, Stephen; Godfrey, Edmund M.; Upponi, Sara S.; Gieseck, Richard L.; de Brito, Miguel Cardoso; Berntsen, Natalie Lie; Gómez-Vázquez, María J.; Ortmann, Daniel; Yiangou, Loukia; et al. (Nature Publishing Group, 2017)
Treatment of common bile duct disorders such as biliary atresia or ischaemic strictures is limited to liver transplantation or hepatojejunostomy due to the lack of suitable tissue for surgical reconstruction. Here, we report a novel method for the isolation and propagation of human cholangiocytes from the extrahepatic biliary tree and we explore the potential of bioengineered biliary tissue consisting of these extrahepatic cholangiocyte organoids (ECOs) and biodegradable scaffolds for transplantation and biliary reconstruction in vivo. ECOs closely correlate with primary cholangiocytes in terms of transcriptomic profile and functional properties (ALP, GGT). Following transplantation in immunocompromised mice ECOs self-organize into tubular structures expressing biliary markers (CK7). When seeded on biodegradable scaffolds, ECOs form tissue-like structures retaining biliary marker expression (CK7) and function (ALP, GGT). This bioengineered tissue can reconstruct the wall of the biliary tree (gallbladder) and rescue and extrahepatic biliary injury mouse model following transplantation. Furthermore, it can be fashioned into bioengineered ducts and replace the native common bile duct of immunocompromised mice, with no evidence of cholestasis or lumen occlusion up to one month after reconstruction. In conclusion, ECOs can successfully reconstruct the biliary tree following transplantation, providing proof-of-principle for organ regeneration using human primary cells expanded in vitro.